MERAJUT TANAMAN OBAT KELUARGA DALAM BINGKAI PENDIDIKAN EKOLOGI - Rogahang, Heldy J.; Heydemans, Nency Aprilia (Tumou Tou, 2019)
This study aims to analyze the results of ecological education research on the use of family medicinal plants in the GMIM Kakaskasen Maranatha Church. Education ranging from children to old age in cultivating family medicinal plants that are believed to have great benefits. Family medicinal plants are useful for preserving nature, the greening movement, herbs and medicines for human health. The method used in this study is a qualitative method with participatory observation techniques, in-depth interviews with four members of the congregation and literature studies such as books, journals, theses, internet. The results of this study indicate that ecological education in cultivating family medicinal plants does not attract the attention of young people, but is of interest to elderly mothers and women to mothers. The impact of ecological education as a marker of human reconciliation with nature. Apart from oneself, church and culture play a role in educating and preserving nature.